PENGEMBANGAN MODEL PENDIDIKAN INTERGRATIF UNTUK MENGATASI MASALAH SOCIAL DISORDER PADA ANAK-ANAK KAMPUNG SRI RAHAYU PURWOKERTO - Titi Anisatul Laely (IAIN Purwokerto, 2015)
Abstract: This study was a qualitative descriptive examines integrative education model development to address the social disorder in children in Kampung Sri Rahayu Purwokerto. Implementation of the development of integrative educational model (Islam, intellectual-cognitive and creative) with the material of playing language, colors, logic, motion and music can provide a change in behavior and mindset in children at Kampung Sri Rahayu. This can be seen when children are in their environment, whether in the home, community, and school. Providing material that is synonymous with playing children make children easily understand and well accept the transfer of knowledge. Integrative education is done through Islamic education by chanting iqra and practice when leaming to make children have intelligent-religious character. The cognitive and creative intellectual education through integrative leaming to play the material language, color, music, logic and motion shaping children to be intelligent This is refiected in the aioton shaping children the and creative. This is reflected in the ability of children in general knowledge and insight into the religion that formed the child to be intelligent. Implementation of project-based leaming that makes children have creative ideas that allow them to solve problems with creative solutions they think of themselves. Keywords: Integrative Education, Social Disorder, Children, Kampung Sri Rahayu.